PERBANDINGAN PEMELIHARAAN AYAM LAYER FASE STARTER STRAIN ISA BROWN DAN HYLINE PADA SISTEM PEMELIHARAAN CLOSE HOUSE - Agung Harianto; Kurniawan Sinaga (Bajang Institute, 2025)
TJudging from the results of this study on the comparison of the maintenance of starter phase layer chickens, Isa Brown and Hyline strains in a close house maintenance system, the aim is to determine the comparison of growth, the influence of the maintenance system and the analysis of calculations (PBB, Feed intake, Uniformity, Mortality) of starter phase layer chickens, Isa Brown and Hyline strains with a close house maintenance system. This study showed the highest PBB results in the sixth week of 13.86 g in the Isa Brown strain and 15.00 in the Hyline strain also in the same week and the highest feed intake in the sixth week with a value of 41 g in the Isa Brown strain and 43 g in the Hyline strain besides that in the analysis of the mortality rate showed the lowest figure in the fifth week of 0.10% in the Isa Brown strain and the sixth week in the Hyline strain of 0.14 with a uniformity level of ≥80% in both strains in each weekly analysis carried out so that the maintenance of starter phase layer chickens with a close house maintenance system provides comparative results on the growth of Isa Brown and Hyline strain layer chickens with fairly good values ​​and in accordance with the growth standards of each strain which is assessed by weekly analysis for six weeks with values, PBB, Mortality, Feed Intake, and Uniformity listed in Table.3 thus that the research conducted succeeded in providing good comparative results with slight differences that are still within the standards of each strain that has been marketed